Activation of Adenovirus Early Promoters and Lytic Phase in Differentiated Strata of Organotypic Cultures of Human Keratinocytes - Noya, Francisco (American Society for Microbiology, 2003)
Human oncolytic adenoviruses have been used in clinical trials targeting cancers of epithelial origin. To gain a better understanding of the infectious cycle of adenovirus in normal human squamous tissues, we examined the viral infection process in organotypic cultures of primary human keratinocytes. We show that for the infection to occur, wounding of the epithelium is required. In addition, infection appears to initiate at the basal or parabasal cells that express the high-affinity coxsackievirus-adenovirus receptor, CAR, whereas the productive phase takes place in differentiated cells. This is due, at least in part, to the differentiation-dependent activation of the E1A and E2A early promoters and E4 promoters. We also show that adenovirus infection triggers a response mediated by the abnormal accumulation of cyclin E and p21cip1 proteins similar to the one previously observed in human papillomavirus-infected tissues. However, the virus seems to be able to overcome it, at least partially.